(untitled) (Bangladesh Pharmaceutical Journal, 2015)
This study was carried out to evaluate the anti-inflammatory and antioxidant activities of Cucumis sativus Linn. (Family: Cucurbitaceae) leaves. The methanolic extract of C. sativus leaves (MCS) was investigated for antiinflammatory activities in Long Evans rat model at two different doses of 150 and 250 mg/kg body weight and the effects were compared with the standard, indomethacin (10 mg/kg body weight). It exhibited highest antiinflammatory activity at the dose 250 mg/kg. In the formalin test, the extract at both doses (150 and 250 mg/kg body weight) significantly prevented the increase in volume of paw edema (P<0.05 and P<0.001). In carrageenan-induced paw edema test the MCS significantly (P?0.001) reduced inflammation by 57.35 % (150 mg/kg body weight) and 72.06% (250 mg/kg body weight) in comparison to the standard drug, indomethacin (79.41%) at the end of 5h. MCS was also screened for DPPH scavenging activity, total antioxidant capacity, reducing ability as well as total phenolics content to assess its antioxidant potential. Total phenolic content and total antioxidant capacity of MCS were found to be 262.31 mg/g equivalent of gallic acid and 267.2 mg/g equivalent of ascorbic acid, respectively. The IC50 of free radical scavenging of DPPH was 13.06 ?g/ml while that of standard ascorbic acid was 13.17 ?g/ml. The reducing power of MCS was found to be concentration dependent. Bangladesh Pharmaceutical Journal 18(2): 169-173, 2015